Interpretation of a Digital Model of the Anomalous Magnetic Field of the Crimean Region and Adjacent Waters, Based on Retrospective Data - Khotenko Elena; Bragina Anastasia; Arutyunyan David; Shklyaruk Alexey (Russian Journal of Earth Sciences)
The article presents the results of work on the interpretation of a digital model of the anomalous magnetic field (AMF) of the Crimean region and adjacent waters, based on retrospective data. For interpretation, a priori data in various fields of geology and geophysics were studied in the public domain. The main interpretation tool was the comparison of the calculated high-frequency and low-frequency magnetic field transformants with a priori geological and geophysical information. Based on the results, a scheme of the tectonic structures of the Crimean region reflected in its magnetic field was constructed.